Restructuring As An Effort To Reduce The Impact Of Problem Financing On Griya Ib Hasanah Produc: Restrukturisasi Sebagai Upaya Mengurangi Dampak Pembiayaan Bermasalah Pada Produk Griya Ib Hasanah - Liaanjani, Devi; Sutikno, Sutikno (Jurnal Keuangan dan Perbankan (KEBAN), 2021)
Impact of non-performing financing on the iB Hasanah home product at BSI KC Cilegon, How is the process of implementing restructuring on Griya iB Hasanah products at BSI KC Cilegon.Purpose : to determine the impact of non-performing financing and restructuring on Griya iB Hasanah products at BSI KC Cilegon.Methodology : This research was conducted using a qualitative descriptive method with the theory of problematic financing restructuring. As for the population, the Indonesian sharia bank KC. Cilegon as many as 2 informants, namely the collection assistant division and the Remedial Recovery Assistant. This research was conducted at Bank Syariah Indonesia KC. Cilegon in April to June. Data were collected through interviews and analyzed by data reduction.Results/Findings : Financing is a bank activity to channel funds to the public. The distribution of funds in the form of financing must be based on the trust given by the bank to customers who want to do financing. Banks must have confidence in customers that the funds provided will run properly and can be paid off, because the risk of financing is a big risk that results in problematic or bad financing. The impact of non-performing financing will disrupt bank operations and liquidity, the increasing NPF will greatly affect the bank and customer confidence in the bank will decrease, the lack of bank ability to expand financing will have a negative impact on the economy.To overcome the problem financing, the bank has a strategy in solving problem financing, namely by way of billing by telephone, giving warning letters or warnings, restructuring, namely Rescheduling, Reconditioning, Restructuring).Paper type : data reductio